Finnish Forest Sector Economic Outlook 2018–2019. Executive Summary - Viitanen, Jari; Mutanen, Antti; Kniivilä, Matleena; Viitala, Esa-Jussi; Kalliovirta, Leena; Härkönen, Kari; Leppänen, Jussi; Uotila, Esa; Routa, Johanna (Natural Resources Institute Finland (Luke), 2018)
Year 2018 will be a major economic peak in the Finnish forest sector. Forest industries’ production and export volumes are growing, industrial roundwood fellings are increasing, stumpage prices are rising, and operating profit in non-industrial private forestry is improving. Current cyclical peak is driven by growing world economy, which has increased the demand for forest industry products. Political decisions, such as restrictions on the import and use of recycled fibre and the closures of polluting mills in China, have contributed to the development of Finnish forest exports. In 2019, the growth in the world economy is expected to slow down. Uncertainty in export markets for forest industry products is maintained by, e.g. the Brexit and problems related to the accumulating debts in China and Italy. Despite the slowdown in the global economic growth, the Finnish forest sector is not expected to face a strong downturn. In 2019, the growth in production and export volumes of forest industry products will slow down for most products and the upward trend in export prices will level off. With regard to market pulp, the export price will decrease from the record high level of 2018.
The executive summary is a translation of the summary of the Finnish original publication, and is based on information available in early October 2018. Available at: http://urn.fi/URN:ISBN:978-952-326-628-5
Keywords: Finland; forestry sector; forest products industry